2022
DOI: 10.1209/0295-5075/ac2455
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor–super-paraelectric behaviour and crystal-field–driven spin-phonon coupling in pyrochlore Eu2Ti2O7

Abstract: The temperature-dependent Raman spectroscopy and dielectric property of pyrochlore Eu2Ti2O7 have been investigated. The appearance of additional phonon modes below 200 K is observed suggesting a local structural change. The anomalous softening of the phonon modes and existence of crystal-field-induced short-range magnetic ordering below 150 K unveiled the possible spin-phonon coupling. The signature behaviour of a dipolar glassy-relaxor state and super-paraelectric nature has been demonstrated. Additional diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[ 27 ] The previous Raman study of ETO also showed that a structural change in ETO occurred below 200 K which is related to the TiO 6 octahedra. [ 28 ] Such octahedral distortion of TiO 6 in similar pyrochlore Ho 2 Ti 2 O 7 was considered to be the key factor for producing the net electrical polarization leading to the relaxor ferroelectricity. [ 49 ] Relaxor ferroelectric material also possesses spontaneous polarization similar to normal ferroelectrics but their domains are very small (of the size of nanolength scale), whereas normal ferroelectric domains are relatively large (of the size of microlength scale).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 27 ] The previous Raman study of ETO also showed that a structural change in ETO occurred below 200 K which is related to the TiO 6 octahedra. [ 28 ] Such octahedral distortion of TiO 6 in similar pyrochlore Ho 2 Ti 2 O 7 was considered to be the key factor for producing the net electrical polarization leading to the relaxor ferroelectricity. [ 49 ] Relaxor ferroelectric material also possesses spontaneous polarization similar to normal ferroelectrics but their domains are very small (of the size of nanolength scale), whereas normal ferroelectric domains are relatively large (of the size of microlength scale).…”
Section: Resultsmentioning
confidence: 99%
“…The previous report on dielectric constant (ε) of ETOF0 shows a strong dielectric relaxation in the form of a broad peak below 150 K, with a maximum value of the relative permittivity (εnormalm) around the temperature ( T m ), which was described as relaxor superparaelectricity. [ 28 ] The superparaelectricity was introduced due to the asymmetric distribution of ε around T m . [ 28 ] Naturally, variation of ε around prefers to be symmetric (Gaussian) profile.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations